2016
DOI: 10.1002/cam4.897
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of definitive concurrent chemoradiotherapy using paclitaxel plus oxaliplatin in unresectable locally advanced esophageal cancer: a prospective phase II trial

Abstract: This prospective study aimed at assessing the efficiency and safety of concurrent chemoradiotherapy (CCRT) using paclitaxel (PTX) plus oxaliplatin (OHP) in unresectable locally advanced esophageal cancer patients. Between January 2006 and December 2010, 34 patients with unresectable locally advanced esophageal cancer were enrolled in this study. Radiotherapy was delivered with a daily fraction of 2.0 Gy to a total dose of 60 Gy over 6 weeks. Concurrent PTX (135 mg/m², d 1) and OHP (130 mg/m², d 1) were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The authors concluded that although dCRT with FOLFOX did not increase PFS and OS compared with dCRT based on 5‐FU and cisplatin, the FOLFOX regimen might be a more convenient treatment option for patients with unresectable EC. Previously, we also reported a phase II clinical trial evaluating the efficiency and safety of dCRT based on OHP and paclitaxel for patients with EC . Our results indicated that 26 (76.5%) of 34 patients finished dCRT on schedule with a median OS of 23.7 months.…”
mentioning
confidence: 58%
“…The authors concluded that although dCRT with FOLFOX did not increase PFS and OS compared with dCRT based on 5‐FU and cisplatin, the FOLFOX regimen might be a more convenient treatment option for patients with unresectable EC. Previously, we also reported a phase II clinical trial evaluating the efficiency and safety of dCRT based on OHP and paclitaxel for patients with EC . Our results indicated that 26 (76.5%) of 34 patients finished dCRT on schedule with a median OS of 23.7 months.…”
mentioning
confidence: 58%
“…The treatment e cacy of de nitive CRT was established by some clinical trials, such as the RTOG 85 − 01 and RTOG 94 − 05 trials [10,11]. Mikhail et al reviewed 12 trials and illustrated that 2year OS of de nitive chemotherapy ranged from 18-54% and 3-year OS ranged from 22.2-64.3% [10,[12][13][14][15][16][17]. The present study reported that 2-/3-year OS were 24.8%/17.8% before matching, and 31.9%/23.8% after matching.…”
Section: Discussionmentioning
confidence: 99%
“…3 For unresected locally advanced ESCC, definitive concurrent chemoradiation therapy (dCCRT) is the standard treatment strategy, and has shown satisfactory clinical effects and manageable toxicities. 4 The standard regimen of dCCRT for ESCC comprises 50.4 Gy of radiation and cisplatinbased chemotherapy, and no significant difference in median survival (13.0 months vs. 18.1 months), 2-year survival (31% vs. 40%), or local/regional failure and persistence of disease (56% vs. 52%) was found between high-dose and standard-dose arms. 5,6 Based on the results of Radiation Therapy Oncology Group (RTOG) 8501, dCCRT significantly increases the survival of patients with EC (T1-3N0-1M0) compared with RT alone (5-year overall survival [OS], 26% vs. 0%, respectively).…”
Section: Introductionmentioning
confidence: 94%